Recent regulatory developments in EU Medical Device Regulation and their impact on biomaterials translation - Klaudia M. Jurczak; Torben A. B. van derBoon; Raul Devia‐Rodriguez; Richte C. L. Schuurmann; Jelmer Sjollema; Lidia vanHuizen; Jean‐Paul P. M. De Vries; Patrick vanRijn (Bioengineering & Translational Medicine, 2025)
Abstract We envision this work to assist researchers and medical device developers (beside other stakeholders) to better understand biomaterial‐based medical device development and its approval process proposed by the new MDR and IVDR in the European Union, as more complex biomaterials emerge, with the MDR reflecting the progress in biomaterial discoveries. Additionally, insufficient international harmonization in regulatory laws and poor‐quality data reporting contribute to the problem. This review describes the possible reasons for a slowing biomaterials translational trend observed over the past decades, focusing on the European Market, and suggests a feasible approach for biomaterials‐based medical device translation into the clinic. Suitable solutions to upgrade biomaterial translation to the clinic have not yet been provided by the field: no additional hurdles should be imposed for researchers, clinicians, the medical device industry, and insurance companies, which all should collaborate on bringing innovative solutions to patients. The new MDR and IVDR represent a substantial advancement in ensuring patient safety and reflect a major step forward in healthcare. However, they should not constrain innovation in biomaterials‐based medical device development. Incorporating reverse engineering from patient safety and a ‘safe by design’ (SbD) strategy early into medical device development might lead to a smoother and successful approval process. A solid R&D phase, with an emphasis on device safety and performance assessment, is fundamental to ensure an effective transition into the clinic. We offer an overview of the recently implemented regulations on medical devices and in vitro diagnostics across the EU, describing a shifting paradigm in the field of biomaterials discovery. As more complex biomaterials emerge, suitable regulations will be necessary to keep bringing safe and well‐performing medical solutions to patients.